Dispersion Parameter Estimation in the Negative Binomial Regression Model with Covariates - Xaychalern1, Kongkeo; Jiewu, Huang (Souphanouvong University Journal Multidisciplinary Research and Development, 2018)
This paper extends the maximum likelihood and bootstrap maximum likelihood methods for dispersion parameter estimation in the negative binomial regression model with covariates. By a Monte Carlo simulation study and a real data analysis, the superiority of the proposed estimators is compared. Furthermore, the influence of covariates and sample size on the estimators of the dispersion parameter is found.